A study of the feasibility of detecting primordial microscopic black hole remnants with the NOvA far detector - Wrobel, Megan, author; Buchanan, Norm, advisor; Berger, Josh, committee member; Adams, Henry, committee member (Colorado State University. Libraries, 2024)
Several papers have argued that microscopic black holes may be stable against complete evaporation and may be a viable dark matter candidate [1–3]. This paper assesses the practicality of detecting these objects using long-baseline neutrino facilities, such as the NuMI Off-Axis νe Appearance (NOvA) experiment and the Deep Underground Neutrino Experiment (DUNE). The origin, stability, properties, and energy loss mechanism of such objects are examined. The signals produced from the detectors should allow for discrimination between these microscopic black holes and other particles traversing the detector. Potential challenges that could arise and next steps are also identified and considered.
Keywords: Hawking radiation; NOvA experiment; black holes; primordial black holes; microscopic black holes